The impact of environment on college students' entrepreneurial intention based on the mediating effect of personality traits - Jiang, Jiping; Xu, Jiapan; Yin, Xiaocui; Hu, Jinyan (Frontiers in Psychology, 2022)
Introduction The entrepreneurship rate of Chinese college students is relatively low. This study investigates the environment factors that influence college students' entrepreneurial intention as mediated by personality traits. Methods According to the entrepreneurial ecosystem theory, a hierarchical model of the environment factors was established which included three layers: personality traits as the micro system, family and education as the meso system, and social and policy support as the macro system. The structural equation model of the environment factors was constructed to reveal the significant influence path of various factors and the mediating role of personality traits. Data were collected from 436 undergraduate students in Henan Province, China. Results Findings indicate that family, education, social, and policy factors have no significant direct influence on entrepreneurial intention. However, personality traits significantly influence entrepreneurial intention and mediate the effects of various factors on entrepreneurial intention. Discussion Suggestions such as improving college students' entrepreneurial practice and promoting college students' proactive personalities are also put forward.